2022
DOI: 10.3390/biology12010073
|View full text |Cite
|
Sign up to set email alerts
|

New Bacillus subtilis Strains Isolated from Prosopis glandulosa Rhizosphere for Suppressing Fusarium Spp. and Enhancing Growth of Gossypium hirsutum L.

Abstract: Rhizobacteria from desert plants can alleviate biotic stress and suppress plant diseases, and consequently can enhance plant growth. Therefore, the current study was performed to isolate and identify Prosopis glandulosa-associating rhizobacteria based on their antagonistic activity against Fusarium species and plant growth-promoting properties. Three bacterial isolates were identified as Bacillus subtilis: LDA-1, LDA-2, and LDA-3. The molecular analysis suggests the biosynthesis of the bacteriocins subtilisin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Interestingly, member of Bacillus has been known as a strong biocontrol agent. Three strains of Bacillus subtilis have been shown to exhibit antagonistic activity against Fusarium in a study concerning cotton plantation [ 88 ]. The inoculation of those bacteria, either individually or in a consortium, has increased antioxidants, phenol, and flavonoid levels, increase stem and root length, promote lateral root formation which might be due to increase in IAA level, and also increase gibberellic acid concentration during the exposure to biotic stress.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, member of Bacillus has been known as a strong biocontrol agent. Three strains of Bacillus subtilis have been shown to exhibit antagonistic activity against Fusarium in a study concerning cotton plantation [ 88 ]. The inoculation of those bacteria, either individually or in a consortium, has increased antioxidants, phenol, and flavonoid levels, increase stem and root length, promote lateral root formation which might be due to increase in IAA level, and also increase gibberellic acid concentration during the exposure to biotic stress.…”
Section: Discussionmentioning
confidence: 99%
“…Some members of the Bacillus genus have been reported to exhibit strong biocontrol activity against various plant pathogens. For example, Abdelmoteleb et al reported that three strains of B. subtilis (LDA-1, 2, and 3) showed highly antagonistic efficacy against phytopathogenic fungi, with percentage inhibition ranging from 43.3% to 83.5% [ 20 ]. In this regard, the results of the dual-culture assay showed that B. subtilis strain LY-1 has potent antifungal activity against F. oxysporum , F. proliferatum , and F. solani , achieving percentage inhibition values of greater than 73.13%, and this effect was higher and more stable than that of other strains previously reported [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The projections predict that climate changes will favor spread of pests and diseases in high-latitude areas (Uleberg et al, 2014). Consequently, negative impacts can be expected due to increased vulnerability of crops to pests and diseases (Pautasso et al, 2012;Abdelmoteleb et al, 2023). The brief descriptions of biotic stresses on crops production are described as under:…”
Section: Biotic Stressesmentioning
confidence: 99%